Proinflammatory cytokine interferon‐γ and microbiome‐derived metabolites dictate epigenetic switch between forkhead box protein 3 isoforms in coeliac disease - Serena, G.; Yan, S.; Camhi, S.; Patel, S.; Lima, R. S.; Sapone, A.; Leonard, M. M.; Mukherjee, R.; Nath, B. J.; Lammers, K. M.; Fasano, A. (Clinical and experimental immunology, 2017)
Summary Coeliac disease (CD) is an autoimmune enteropathy triggered by gluten and characterized by a strong T helper type 1 (Th1)/Th17 immune response in the small intestine. Regulatory T cells (Treg) are CD4+CD25++forkhead box protein 3 (FoxP3+) cells that regulate the immune response. Conversely to its counterpart, FoxP3 full length (FL), the alternatively spliced isoform FoxP3 Δ2, cannot properly down‐regulate the Th17‐driven immune response. As the active state of CD has been associated with impairments in Treg cell function, we aimed at determining whether imbalances between FoxP3 isoforms may be associated with the disease. Intestinal biopsies from patients with active CD showed increased expression of FOXP3 Δ2 isoform over FL, while both isoforms were expressed similarly in non‐coeliac control subjects (HC). Conversely to what we saw in the intestine, peripheral blood mononuclear cells (PBMC) from HC subjects did not show the same balance between isoforms. We therefore hypothesized that the intestinal microenvironment may play a role in modulating alternative splicing. The proinflammatory intestinal microenvironment of active patients has been reported to be enriched in butyrate‐producing bacteria, while high concentrations of lactate have been shown to characterize the preclinical stage of the disease. We show that the combination of interferon (IFN)‐γ and butyrate triggers the balance between FoxP3 isoforms in HC subjects, while the same does not occur in CD patients. Furthermore, we report that lactate increases both isoforms in CD patients. Collectively, these findings highlight the importance of the ratio between FoxP3 isoforms in CD and, for the first time, associate the alternative splicing process mechanistically with microbial‐derived metabolites. Celiac disease is an autoimmune enteropathy triggered by the ingestion of gluten. We show that the intestinal microenvironment that characterize the preclinical and active state of the disease plays a role in modulating the ratio between FOXP3 isoforms and, for the first time, we mechanistically associate the alternative splicing process with microbial derived metabolites.